Commercial Law - The National Assembly (2005)
Commercial activities conducted in the territory of the Socialist Republic of Vietnam. Commercial activities conducted outside the territory of the Socialist Republic of Vietnam in cases where the involved parties agree to this Law for application, or where a foreign law or a treaty to which the Socialist Republic of Vietnam is a contracting party stipulates the application of this Law. Activities not for profit purposes conducted by a party in its transactions with traders in the territory of the Socialist Republic of Vietnam in cases where the party conducting such not-for-profit activities chooses to apply this Law.